К проблеме воспитания и обучения детей со сложными нарушениями развития - Азарян, Р. Н.; Азатян, Т. Ю.
The article presents the need to develop a uniform syst em of classifi cation for children with multiple disorders of development . The off ered approaches for © ecial education for children in a family, and also ways of socialization into society.
Keywords: Дети со сложными нарушениями развития